Fabrication and Analysis of Polydimethylsiloxane (PDMS) Microchannels for Biomedical Application - Shahzadi Tayyaba (16493946) (2020)
In this research work, Polydimethylsiloxane (PDMS) has been used for the fabrication of microchannels for biomedical application. Under the internet of things (IoT)-based controlled environment, the authors have simulated and fabricated bio-endurable, biocompatible and bioengineered PDMS-based microchannels for varicose veins implantation exclusively to avoid tissue damaging. Five curved ascending curvilinear micro-channel (5CACMC) and five curved descending curvilinear micro-channels (5CDCMC) are simulated by MATLAB (The Math-Works, Natick, MA, USA) and ANSYS (ANSYS, The University of Lahore, Pakistan) with actual environments and confirmed experimentally. The total length of each channel is 1.6 cm. The diameter of both channels is 400 µm. In the ascending channel, the first to fifth curve cycles have the radii of 2.5 mm, 5 mm, 7.5 mm, 10 mm, and 2.5 mm respectively. In the descending channel, the first and second curve cycles have the radii of 12.5 mm and 10 mm respectively. The third to fifth cycles have the radii of 7.5 mm, 5 mm, and 2.5 mm respectively. For 5CACMC, at Reynolds number of 185, the values of the flow rates, velocities and pressure drops are 19.7 µLs−1, 0.105 mm/s and 1.18 Pa for Fuzzy simulation, 19.3 µLs−1, 0.1543 mm/s and 1.6 Pa for ANSYS simulation and 18.23 µLs−1, 0.1332 mm/s and 1.5 Pa in the experiment. For 5CDCMC, at Reynolds number 143, the values of the flow rates, velocities and pressure drops are 15.4 µLs−1, 0.1032 mm/s and 1.15 Pa for Fuzzy simulation, 15.0 µLs−1, 0.120 mm/s and 1.22 Pa for ANSYS simulation and 14.08 µLs−1, 0.105 mm/s and 1.18 Pa in the experiment. Both channels have three inputs and one output. In order to observe Dean Flow, Dean numbers are also calculated. Therefore, both PDMS channels can be implanted in place of varicose veins to have natural blood flow. Other Information Published in: Processes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/pr9010057